PENGARUH SERVANT LEADERSHIP DAN KOMITMEN ORGANISASI TERHADAP PENINGKATAN KINERJA (STUDI KASUS PADA PEGAWAI DI KELURAHAN PEKAYON JAYA, KEC. BEKASI SELATAN, KOTA BEKASI) - Donalan Giyanti; Novita Wahyu Setyowati; Agus Dharmanto (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine and analyze whether there is an effect of Servant Leadership and Organizational Commitment Empowerment on improving employee performance in Pekayon Jaya villages . This study uses primary data, namely by distributing questionnaires to employees who work in Pekayon Jaya Village. With a saturated sampling technique that uses the entire population as a sample, namely 38 employees. Data analysis techniques in this study include validity test, reliability test, descriptive statistical test, classic assumption test (normality test, multicollinearity, heteroscedasticity, multiple regression analysis test, hypothesis test (t test, f test) and determination coefficient test (R2) with The significance level is 5% by using the SPSS ver 23 application. Based on the results of the partial test using the t test, it can be seen that the Servant Leadership and Organizational Commitment resources has a positive and significant effect on performance improvement. And simultaneously Servant Leadership and Organizational Commitment contributed to an increase in performance namely by 80.3%, where the remaining 19.7% could be influenced by other factors or variables outside the variables studied.